Faktor-Faktor yang Berhubungaan dengan Pemeriksaan IVA di Wilayah Kerja Puskesmas Muara Beliti Kabupaten Musi Rawas - Wulan, Susilo; Sanisahhuri, Sanisahhuri; Syavani, Dini; Wulandari, Elza; Ravida, Ravida; Hanifah, Hanifah (Universitas Malahayati, 2024)
ABSTRACT Cervical cancer is a disease process that starts when abnormal cells are changed by a genetic mutation of cellular Deaxyribo Nucletic Acid (DNA). About 90% of cervical cancer deaths occur in low and middle income countries. This study aims to study the relationship between husband's motivation and support with IVA examinations in the working area of the Muara Beliti Community Health Center, Musi Rawas Regency. This study used an analytic survey approach with a cross sectional design. The population in this study were all PUS in the Work Area of the Muara Beliti Community Health Center, Musi Rawas Regency in August-September 2020 as many as 4889 people using purposive sampling technique of 98 people. Collecting data in this study using primary data, distributing questionnaires and secondary data documentation from the Health Office. Data analysis was performed using the Chi-Square test (χ2) and the Contingency Coefficient test (C). Obtained Of the 98 samples there were 62 (63%) people who did not undergo IVA examination; Of the 98 samples, there are 54 (55.1%) people with favorable motivation; Of the 98 samples, 50 (51.0%) supported husbands; There is a significant relationship between motivation and IVA examination in the working area of the Muara Beliti Community Health Center, Musi Rawas Regency, with a moderate relationship category; There is a significant relationship between husband's support and IVA examination in the working area of the Muara Beliti Community Health Center, Musi Rawas Regency, with a moderate relationship category. It is hoped that the puskesmas will increase the motivation and insight of the community about the importance of IVA examinations through good health promotion and education at both the puskesmas and posyandu. Keywords: Motivation, Husband's Support, IVA Test ABSTRAK Kanker serviks adalah proses penyakit yang bermula ketika sel abnormal diubah oleh mutasi genetik dari Deaxyribo Nucletic Acid (DNA) selular. Sekitar 90% kematian akibat kanker serviks terjadi di negara-negara berpenghasilan rendah dan menengah. Penelitian ini bertujuan untuk mempelajari hubungan motivasi dan dukungan suami dengan pemeriksaan IVA di wilayah kerja Puskesmas Muara Beliti Kabupaten Musi Rawas. Penelitian ini menggunakan pendekatan survey analitik dengan rancangan Cross Sectional. Populasi dalam penelitian ini adalah semua PUS di Wilayah Kerja Puskesmas Muara Beliti Kabupaten Musi Rawas pada bulan Agustus-September Tahun 2020 sebanyak 4889 orang dengan teknik pengambilan menggunakan Purposive Sampling diperoleh 98 orang. Pengumpulan data dalam penelitian ini yaitu menggunakan data primer penyebaran kuesioner dan data sekunder dokumentasi dari Dinas Kesehatan. Analisis data dilakukan dengan uji Chi-Square (χ2) dan Uji Contingency Coefficient (C). Dari 98 sampel terdapat 62 (63%) orang tidak dilakukan pemeriksaan IVA; Dari 98 sampel terdapat 54 (55,1%) orang motivasi favourable; Dari 98 sampel terdapat 50 (51,0%) orang suami mendukung; Ada hubungan yang signifikan antara motivasi dengan pemeriksaan IVA di wilayah kerja Puskesmas Muara Beliti Kabupaten Musi Rawas, dengan kategori hubungan sedang; Ada hubungan yang signifikan antara dukungan suami dengan pemeriksaan IVA di wilayah kerja Puskesmas Muara Beliti Kabupaten Musi Rawas, dengan kategori hubungan sedang. Diharapkan kepada pihak puskesmas dapat meningkatkan motivasi dan wawasan masyarakat tentang pentingnya pemeriksaan IVA melalui promosi kesehatan baik dan edukasi puskesmas maupun posyandu. Kata Kunci: Motivasi, Dukungan Suami, Pemeriksaan IVA